Nanoscale enhancement of photoconductivity by localized charge traps in the grain structures of monolayer MoS2. Issue 1 (December 2018) - Yang, Myungjae; Kim, Tae-Young; Lee, Takhee; Hong, Seunghun
Abstract We report a method for mapping the nanoscale anomalous enhancement of photoconductivity by localized charge traps in the grain structures of a molybdenum disulfide (MoS2 ) monolayer. In this work, a monolayer MoS2 film was laterally scanned by a nanoscale conducting probe that was used to make direct contact with the MoS2 surface. Electrical currents and noise maps were measured through the probe. By analyzing the data, we obtained maps for the sheet resistance and charge trap density for the MoS2 grain structures. The maps clearly show grains for which sheet resistance and charge trap density were lower than those of the grain boundaries. Interestingly, we found an unusual inverse proportionality between the sheet resistance and charge trap density in the grains, which originated from the unique role of sulfur vacancies acting as both charge hopping sites and traps in monolayer MoS2 . In addition, under light illumination, the larger the trap density of a region was, the larger the photocurrent of the region was, indicating anomalous enhancement of the photocurrent by traps. Since our method provides valuable insights to understand the nanoscale effects of traps on photoconductive charge transport, it can be a powerful tool for noise studies and the practical application of two-dimensional materials.